The Transcriptional Landscape of Microglial Genes in Aging and Neurodegenerative Disease - Bonham, Luke W.; Sirkis, Daniel W.; Yokoyama, Jennifer S. (Frontiers in Immunology, 2019)
Microglia, the brain-resident myeloid cells, are strongly implicated in Alzheimer’s disease (AD) pathogenesis by human genetics. However, the mechanisms by which microglial gene expression is regulated in a region-specific manner over the course of normal aging and in neurodegenerative disease are only beginning to be deciphered. Herein, we used a specific marker of microglia (TMEM119) and a cell-type expression profiling tool (CellMapper) to identify a human microglial gene expression module. Surprisingly, we found that microglial module genes are robustly expressed in several healthy human brain regions known to be vulnerable in AD, in addition to other regions affected only later in disease or spared in AD. Surveying the microglial gene set for differential expression over the lifespan in mouse models of AD and a related tauopathy revealed that the majority of microglial module genes were significantly upregulated in cortex and hippocampus as a function of age and transgene status. Extending these results, we also observed significant upregulation of microglial module genes in several AD-affected brain regions in addition to other regions using postmortem brain tissue from human AD samples. In pathologically confirmed AD cases, we found preliminary evidence that microglial genes may be dysregulated in a sex-specific manner. Finally, we identified specific and significant overlap between the described microglial gene set—identified by unbiased co-expression analysis—and genes known to impart risk for AD. Our findings suggest that microglial genes show enriched expression in AD-vulnerable brain regions, are upregulated during aging and neurodegeneration in mice, and are upregulated in pathologically affected brain regions in AD. Taken together, our data-driven findings from multiple publicly accessible datasets reemphasize the importance of microglial gene expression alterations in AD and, more importantly, suggest that regional and sex-specific variation in microglial gene expression may be implicated in risk for and progression of neurodegenerative disease.